Electrodes, electrochemical devices and electronic devices
By using a cage-shaped network formed by carbon nanotubes in the electrodes to encapsulate the active material, the problem of insufficient energy density of existing electrochemical devices is solved, and higher conductivity and energy density are achieved, while avoiding the adverse effects of the binder.
Patent Information
- Application Number
- CN202180031182.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-12-08
AI Technical Summary
The energy density of existing electrochemical devices is still unsatisfactory, and while increasing the capacity or voltage of the active material, it is difficult to effectively reduce the content of the inactive material.
By introducing rope-shaped carbon nanotube aggregates formed by carbon nanotubes into the electrodes, interwoven to form a cage-like network, enclosing the active material, thereby enhancing conductivity and structural stability and reducing the proportion of inactive materials.
The conductivity and structural stability of the electrode active material layer are improved, the rate performance and energy density are enhanced, and the negative impact of the adhesive on the conductivity is avoided.
Smart Images

Figure CN115552665B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to electrodes, electrochemical devices and electronic devices. Background Art
[0002] Electrochemical devices, such as lithium-ion batteries, have the advantages of high energy density, high power, and long cycle life. They are widely used in various fields. With the development of technology, the requirements for the energy density of electrochemical devices are getting higher and higher. In order to improve the energy density of electrochemical devices, some technologies increase the capacity or voltage of active materials, while other technologies increase the content of active materials per unit volume and reduce the content of inactive materials. The proportion of inactive substances can be reduced by reducing the thickness of the current collector or isolation membrane, reducing the proportion of inactive materials in the formula, and preparing thicker electrodes, but the existing improvement methods are still unsatisfactory, and further improvements are expected. Summary of the invention
[0003] Some embodiments of the present application provide an electrode, an electrochemical device, and an electronic device.
[0004] In some embodiments of the present application, an electrode is provided, the electrode comprising a current collector and an active material layer located on one side or both sides of the current collector, the active material layer comprising an active material and a conductive agent; the conductive agent comprises carbon nanotubes, and the active material layer comprises rope-shaped carbon nanotube aggregates formed by carbon nanotubes, interweaving to form a cage-shaped network, and the active material is wrapped inside the cage-shaped network. In some embodiments, the particles of the active material are entangled by the rope-shaped carbon nanotube aggregates, thereby enhancing the long-range conductivity of the active material layer and improving the stability of the structure, which is conducive to increasing the thickness of the active material layer to improve the energy density.
[0005] In some embodiments of the present application, based on the total mass of the active material layer, the mass percentage of the carbon nanotube aggregates is 0.5% to 5%. In some embodiments, if the mass percentage of the carbon nanotube aggregates is too low, it is not conducive to conductivity, and if the mass percentage of the carbon nanotube aggregates is too high, it may affect the volume capacity.
[0006] In some embodiments of the present application, the carbon nanotube aggregate has a rope-like structure formed by 2 to 1000 carbon nanotubes entangled with each other, thereby improving the structural stability and thus playing the effect of stabilizing the active material layer.
[0007] In some embodiments of the present application, the diameter of the carbon nanotube is 0.5 nm to 10 nm, and the length is 1 μm to 100 μm. In some embodiments, a carbon nanotube with a diameter that is too small or a length that is too short is not conducive to improving the structural stability of the active material layer, and a carbon nanotube with a diameter that is too large or a length that is too large is easy to break.
[0008] In some embodiments of the present application, the diameter of the carbon nanotube aggregate is 1nm to 1000nm, and the length is 1μm to 100μm. In some embodiments, the diameter and length of the carbon nanotube aggregate are too small, which is not conducive to improving the structural stability of the active material layer, while the diameter or length is too large and it is easy to break.
[0009] In some embodiments of the present application, the thickness of the carbon nanotube aggregates on the surface of the particles of the active material is 10nm to 1000nm. In some embodiments, if the thickness of the carbon nanotube aggregates on the surface of the particles of the active material is too small, the particles of the active material may not be well fixed, and if the thickness is too large, the volume energy density may be affected.
[0010] In some embodiments of the present application, a network gap in the cage network includes 1 to 50 particles of active material. In some embodiments, if there are too many active materials in a network gap of the cage network, the improvement in conductivity may not be obvious. If there are no particles of active material in the network pores, the volume energy density will be reduced. In some embodiments of the present application, the Dv50 of the active material is 1 μm to 30 μm. In some embodiments, a Dv50 of the active material that is too small may affect the cycle performance, and a Dv50 that is too large may affect the rate performance.
[0011] In some embodiments of the present application, the electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the compaction density ρ1 of the positive electrode active material layer is ≥3.0 g / cm 3 In some embodiments, a larger compaction density is beneficial to improving the energy density of the positive electrode active material layer. In some embodiments, the porosity n1 of the positive electrode active material layer satisfies: 20% ≥ n1 ≥ 15%. In some embodiments, too small a porosity may result in insufficient electrolyte infiltration, and too high a porosity may result in a decrease in volume energy density. In some embodiments, the resistivity of the positive electrode active material layer is: 0.1Ω*㎝ to 100Ω*㎝. In some embodiments, the bonding force of the positive electrode active material layer is ≥ 1N / m. In some embodiments, the active material is a positive electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium-rich material, sulfur or sulfur-based compounds. In some embodiments of the present application, the electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the compaction density ρ1 of the positive electrode active material layer satisfies: 4.25g / cm 3 ≥ρ1≥2.3g / cm 3 .
[0012] In some embodiments of the present application, the electrode is a negative electrode, the current collector is a negative electrode current collector, the active material layer is a negative electrode active material layer, and the compaction density ρ2 of the negative electrode active material layer is ≥1.3 g / cm 3. In some embodiments, a larger compaction density is beneficial to improving the volume energy density. In some embodiments, the porosity n2 of the negative electrode active material layer satisfies: 35% ≥ n2 ≥ 25%, thereby ensuring the infiltration of the electrolyte while ensuring the energy density. In some embodiments, the resistivity of the negative electrode active material layer is 0.01Ω*㎝ to 50Ω*㎝. In some embodiments, the bonding force of the negative electrode active material is ≥1N / m. In some embodiments, the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon-based material, tin-based material, lithium metal material or carbon material. In some embodiments of the present application, the electrode is a negative electrode, the active material layer is a negative electrode active material layer, and the compaction density ρ2 of the negative electrode active material layer satisfies: 1.85g / cm 3 ≥ρ2≥1.35g / cm 3 .
[0013] The present application provides an electrochemical device, comprising an electrode: the electrode is any electrode in the present application.
[0014] The present application provides an electronic device, including the electrochemical device provided in the present application.
[0015] An electrode proposed in an embodiment of the present application; the electrode includes a current collector and an active material layer located on one side or both sides of the current collector, the active material layer includes an active material and a conductive agent; the conductive agent includes carbon nanotubes, and the active material layer includes rope-shaped carbon nanotube aggregates formed by carbon nanotubes, the carbon nanotube aggregates are interwoven to form a cage-like network, and the active material is wrapped inside the cage-like network. The particles of the active material are wrapped by the carbon nanotube aggregates, thereby enhancing the long-range conductivity of the active material layer and improving the stability of the structure, which is conducive to improving the rate performance and energy density of the active material layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The above and other features, advantages and aspects of the embodiments of the present disclosure will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. Throughout the accompanying drawings, the same or similar reference numerals represent the same or similar elements. It should be understood that the drawings are schematic and that components and elements are not necessarily drawn to scale.
[0017] Figure 1 is a schematic diagram of an electrode according to an embodiment of the present disclosure.
[0018] Figure 2 is a scanning electron microscope image of an active material layer of an embodiment of the present disclosure. DETAILED DESCRIPTION
[0019] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.
[0020] The electrode in the electrochemical device is obtained by stirring and mixing the active material, conductive agent, binder and additive in a solvent, coating the mixture on the current collector, and drying and rolling the mixture to obtain the electrode. The presence of the binder in the electrode not only reduces the energy density, but also the binder does not conduct electrons and ions. The presence of the binder hinders the transmission of electrons and ions between the active material and the current collector, increases the movement distance of electrons and ions, and thus limits the rate performance. The presence of the binder will also lead to an increase in the volume of the active material layer, thereby reducing the volume energy density of the electrode active material layer. Therefore, the development of a binder-free electrode is an urgent problem to be solved.
[0021] In some technologies, a thin coating method is used to prepare the precursor of the active material into a solution, apply it on the surface of the current collector, and heat it to generate the active material in situ on the surface of the current collector to form a binder-free electrode with a thickness of less than 10 μm. In other technologies, a photo-in-situ preparation technology is used, and a laser is used to irradiate the precursor of the graphene oxide and SnO2 sol mixture pre-coated on the copper foil in an environment with a protective gas. Through the photochemical reaction triggered by the laser, the precursor is converted into a graphene / Sn-based composite material in situ, and a one-step preparation of a graphene / SnO2 nanocomposite electrode is achieved. In other technologies, chemical vapor deposition combined with hydrothermal reaction technology is used to manufacture a seamless three-dimensional graphene network on nickel foam by chemical vapor deposition, which can simultaneously achieve excellent conductivity and large specific surface area. Hydrothermal reaction growth of vertically arranged nickel-cobalt selenide nanosheets on three-dimensional graphene / nickel foam can provide this network structure with a larger surface active area and abundant electroactive sites, shortening the transmission path of ion diffusion.
[0022] However, in the thin coating method, the thickness of the active material layer on the current collector surface is less than 10μm, and the number of battery cells of the same thickness is more, the proportion of inactive materials increases, and the energy density is reduced. As the thickness increases, the bonding force between the active material and the current collector weakens, which makes it easy to peel off and deteriorate the performance. In the laser in-situ preparation technology, the graphene / Sn-based composite materials are mainly transformed by the photochemical reaction induced by the laser. Due to the uneven distribution of laser energy along the thickness direction, it is easy to cause uneven conversion of the composite materials. In the chemical vapor deposition combined with hydrothermal reaction technology, the preparation process is complicated and the consistency is difficult to control.
[0023] In order to solve the technical problems encountered when improving the energy density of electrochemical devices in some embodiments of the present application, a binder-free electrode with no deterioration in electrical performance is proposed, which can improve electron and ion conduction, and enhance rate performance and energy density.
[0024] In some embodiments of the present application, an electrode is provided, the electrode comprising a current collector and an active material layer located on one side or both sides of the current collector, the active material layer comprising an active material and a conductive agent; the conductive agent comprises carbon nanotubes, the active material layer comprises rope-shaped carbon nanotube aggregates formed by carbon nanotubes, the carbon nanotube aggregates are interwoven to form a cage-shaped network, and the active material is wrapped inside the cage-shaped network. In some embodiments, the particles of the active material are wrapped by the rope-shaped carbon nanotube aggregates, thereby enhancing the long-range conductivity of the active material layer and improving the stability of the structure, which is conducive to improving the rate performance and energy density of the active material layer.
[0025] In some embodiments of the present application, the electrode does not contain a binder, thereby reducing the mass and volume occupied by the binder, increasing the energy density, and avoiding the influence on the conductivity caused by the addition of the binder. On the other hand, the particles of the active material are wrapped by rope-like carbon nanotube aggregates, which improves the stability of the structure and avoids the problem of instability of the active material layer structure caused by not adding a binder, thereby helping to improve the conductivity of the active material layer, and helping to improve the energy density without deteriorating the electrical performance.
[0026] In some embodiments of the present application, based on the total mass of the active material layer, the mass percentage of the carbon nanotube aggregates is 0.5% to 5%. In some embodiments, the content of the carbon nanotube aggregates will affect the conductivity of the active material layer and the energy of the active material layer. If the mass percentage of the carbon nanotube aggregates is too low, it will be detrimental to the conductivity. If the mass percentage of the carbon nanotube aggregates is too high, it may affect the volume capacity.
[0027] In some embodiments of the present application, the carbon nanotube aggregate has a rope-like structure formed by 2 to 1000 carbon nanotubes entangled with each other. The rope-like structure formed by at least 2 carbon nanotubes entangled with each other enhances the structural strength and improves the structural stability, thereby stabilizing the active material layer.
[0028] In some embodiments of the present application, the diameter of the carbon nanotube is 0.5 nm to 10 nm, and the length is 1 μm to 100 μm. In some embodiments, a carbon nanotube with a diameter that is too small or a length that is too short is not conducive to improving the structural stability of the active material layer, and a carbon nanotube with a diameter that is too large or a length that is too large is easy to break.
[0029] In some embodiments of the present application, the diameter of the carbon nanotube aggregate is 1nm to 1000nm, and the length is 1μm to 100μm. In some embodiments, if the diameter and length of the carbon nanotube aggregate are too small, it is not conducive to improving the structural stability of the active material layer. If the diameter or length is too large, it is easy to break and may affect the energy density of the active material layer.
[0030] In some embodiments of the present application, the thickness of the carbon nanotube aggregates on the surface of the particles of the active material is 10nm to 1000nm. In some embodiments, if the thickness of the carbon nanotube aggregates on the surface of the particles of the active material is too small, the particles of the active material may not be well fixed, which is not conducive to improving the stability of the active material layer. If the thickness of the carbon nanotube aggregates is too large, the volume energy density may be affected.
[0031] In some embodiments of the present application, a network gap in the cage network includes 1 to 50 particles of active material. In some embodiments, if there are too many active materials in a network gap of the cage network, there may be too large a distance between more particles and carbon nanotubes, which may result in an insignificant improvement in conductivity. If there are no particles of active material in the network pores, the amount of active material per unit volume is reduced, thereby reducing the volume energy density.
[0032] In some embodiments of the present application, the Dv50 of the active material is 1 μm to 30 μm. In some embodiments, if the Dv50 of the active material is too small, the cycle performance may be affected, and if the Dv50 is too large, the rate performance may be affected.
[0033] In some embodiments of the present application, the electrode is a positive electrode, the current collector is a positive electrode current collector, such as copper foil or aluminum foil, the active material layer is a positive electrode active material layer, and the compaction density ρ1 of the positive electrode active material layer is ≥3.0 g / cm 3 In some embodiments, a larger compaction density is beneficial to improving the energy density of the positive electrode active material layer. However, too large a compaction density may cause the particles of the active material to break, which is not conducive to the cycle performance. Therefore, in some embodiments, the compaction density ρ1 of the positive electrode active material layer satisfies: 4.25 g / cm 3 ≥ρ1≥2.3g / cm 3 , while ensuring energy density and preventing the particles of active materials from breaking.
[0034] In some embodiments, the porosity n1 of the positive electrode active material layer satisfies: 20% ≥ n1 ≥ 15%. In some embodiments, a porosity that is too small may result in insufficient electrolyte infiltration, affecting the performance of the active material, and a porosity that is too high may result in a reduction in volume energy density. In some embodiments, the resistivity of the positive electrode active material layer is: 0.1Ω*㎝ to 100Ω*㎝. The resistivity reflects the conductivity of the positive electrode active material layer, which indicates that the positive electrode active material layer in the embodiment of the present application has good conductivity. In some embodiments, the bonding force of the positive electrode active material layer is ≥ 1N / m, thereby preventing the separation between the positive electrode active material layer and the positive electrode current collector.
[0035] In some embodiments, the active material is a positive electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium-rich material, sulfur or sulfur-based compounds, for example, it can be one, two or more thereof.
[0036] In some embodiments of the present application, the electrode is a negative electrode, the current collector is a negative electrode current collector, such as copper foil or aluminum foil, the active material layer is a negative electrode active material layer, and the compaction density ρ2 of the negative electrode active material layer is ≥1.3 g / cm 3 In some embodiments, a larger compaction density is beneficial to improve the volume energy density. In some embodiments, too large a compaction density may cause the active material particles to break, increase the consumption of the electrolyte and deteriorate the cycle performance. Therefore, in some embodiments, the compaction density ρ2 of the negative electrode active material layer satisfies: 1.85 g / cm 3 ≥ρ2≥1.35g / cm 3 .
[0037] In some embodiments, the porosity n2 of the negative electrode active material layer satisfies: 35% ≥ n2 ≥ 25%, so that the porosity is large enough to ensure the wettability of the electrolyte, while limiting the porosity to prevent the energy density from being affected. In some embodiments, the resistivity of the negative electrode active material layer is 0.01Ω*㎝ to 50Ω*㎝, which is conducive to ensuring conductivity. In some embodiments, the bonding force of the negative electrode active material is ≥ 1N / m to prevent the negative electrode active material layer from detaching from the negative electrode current collector. In some embodiments, the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon-based material, tin-based material, lithium metal material or carbon material.
[0038] In some embodiments of this application, please refer to Figure 1 and Figure 2 The electrode includes a current collector 10 and an active material layer, the active material layer includes active material particles 20 and carbon nanotube aggregates 30, the carbon nanotube aggregates 30 form a cage-like grid, the carbon nanotube aggregates 30 can be wrapped around the surface of the active material particles, or there can be gaps between the active material particles, and the active material particles are wrapped in the cage-like structure. In some embodiments of the present application, the electrode does not contain a binder, and the carbon nanotube aggregates 30 increase the long-range electronic conductivity, while avoiding the binder from hindering ion transmission, improving the kinetic performance, and being conducive to improving the rate performance and energy density.
[0039] There are many methods for preparing the electrodes in the embodiments of the present application, which are exemplified below.
[0040] Method 1: Add carbon nanotubes and photosensitive dispersants into a dispersion medium, form a uniform dispersion by ultrasonic, stirring, sand milling and other methods, mix the active material and carbon nanotube dispersion in proportion and disperse them to form a slurry, apply the slurry to at least one surface of the current collector and dry it, and then treat it with light to form a binder-free electrode.
[0041] Method 2: The active material and the carbon nanotube dispersion are mixed and dispersed to form a slurry, and the slurry is coated on at least one surface of the current collector and dried to form a binder-free electrode.
[0042] In some embodiments of the present application, the electrochemical device includes an electrode, and the electrode can be an electrode in any embodiment of the present application. In some embodiments, the electrochemical device includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. In some embodiments, the positive electrode or the negative electrode can be any of the above electrodes. In some embodiments, the current collector of the positive electrode can be Al foil, and of course, other current collectors commonly used in the art can also be used.
[0043] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 50 μm.
[0044] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.
[0045] In some embodiments of the present application, the electrochemical device may be wound or stacked. In some embodiments, the positive electrode and / or negative electrode of the electrochemical device may be a multilayer structure formed by winding or stacking, or a single-layer structure in which a single-layer positive electrode, a separator, and a single-layer negative electrode are stacked.
[0046] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it has high ionic conductivity and can improve cycle characteristics.
[0047] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.
[0048] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0049] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0050] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0051] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.
[0052] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode, a separator, and a negative electrode are wound or stacked in sequence to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.
[0053] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.
[0054] The present application proposes an electronic device, including an electrochemical device; the electrochemical device is an electrochemical device of any one of the present application. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera or a large household battery, etc.
[0055] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.
[0056] Example 1
[0057] Preparation of positive electrode sheet: The positive electrode material lithium cobalt oxide and carbon nanotubes (CNT) are mixed in a mass ratio of 99.5:0.5, and N-methylpyrrolidone (NMP) is used as a solvent to prepare a slurry, which is stirred evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet. The thickness of the positive electrode active material layer on one side of the positive electrode current collector is 63μm.
[0058] Preparation of negative electrode sheet: negative electrode materials graphite, styrene acrylate and sodium carboxymethyl cellulose were mixed in a mass ratio of 97.6:1.2:1.2, deionized water was used as solvent to form a negative electrode active material layer slurry, copper foil was used as the negative electrode current collector, and the slurry of the negative electrode active material layer was coated on the negative electrode current collector. The thickness of the negative electrode active material layer on one side of the negative electrode current collector was 75 μm, and the compaction density was 1.75 g / cm 3 , and dried at 90°C to obtain the negative electrode sheet.
[0059] Preparation of isolation film: The isolation film is 8 μm thick polyethylene (PE).
[0060] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, weight ratio) are prepared in a weight ratio of 8:92 to form an electrolyte.
[0061] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.
[0062] Examples 2 to 11 are based on the preparation steps of Example 1 with parameter changes, and the specific changed parameters are shown in the table below.
[0063] Example 12
[0064] Preparation of positive electrode sheet: Mix the positive electrode materials lithium cobalt oxide, polyvinylidene fluoride (PVDF) and conductive carbon black (Super P) in a mass ratio of 97.5:1.5:1.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into a slurry, and stir evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet. The thickness of the positive electrode active material layer on one side of the positive electrode current collector is 63μm, and the compaction density is 4.15g / cm 3 .
[0065] Preparation of negative electrode sheet: negative electrode material graphite and carbon nanotubes (CNT) were mixed in a mass ratio of 99.5:0.5, deionized water was used as solvent to form negative electrode active material layer slurry, copper foil was used as negative electrode current collector, and the negative electrode active material layer slurry was coated on the negative electrode current collector. The thickness of the negative electrode active material layer on one side of the negative electrode current collector was 75 μm, and the compaction density was 1.75 g / cm 3 , and dried at 90°C to obtain the negative electrode sheet.
[0066] The remaining preparation steps of Example 12 are the same as those of Example 1.
[0067] Examples 13 to 22 are based on the preparation steps of Example 12 with parameter changes, and the specific changed parameters are shown in the table below.
[0068] Examples 23 to 29 are based on the preparation steps of Example 1 with parameter changes, and the specific changed parameters are shown in the table below.
[0069] Examples 30 to 37 are based on the preparation steps of Example 12 with parameter changes, and the specific changed parameters are shown in the table below.
[0070] Embodiment 38
[0071] Preparation of positive electrode sheet: The positive electrode material lithium cobalt oxide and carbon nanotubes (CNT) are mixed in a mass ratio of 98.5:1.5, and N-methylpyrrolidone (NMP) is used as a solvent to prepare a slurry, which is stirred evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet. The thickness of the positive electrode active material layer on one side of the positive electrode current collector is 63μm.
[0072] Preparation of negative electrode sheet: negative electrode material graphite and carbon nanotubes (CNT) were mixed in a mass ratio of 98.5:1.5, deionized water was used as solvent to form negative electrode active material layer slurry, copper foil was used as negative electrode current collector, and the negative electrode active material layer slurry was coated on the negative electrode current collector. The thickness of the negative electrode active material layer on one side of the negative electrode current collector was 75 μm, and the compaction density was 1.75 g / cm 3 , and dried at 90°C to obtain the negative electrode sheet.
[0073] The remaining preparation steps of Example 38 are the same as those of Example 1.
[0074] Comparative Example 1
[0075] Preparation of positive electrode sheet: Mix the positive electrode material lithium cobalt oxide, binder polyvinylidene fluoride (PVDF), and conductive carbon black (SuperP) in a mass ratio of 97.5:1.5:1.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into slurry, and stir evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet.
[0076] The remaining preparation steps of Comparative Example 1 are the same as those of Example 1, and the specific parameter differences are shown in the table below.
[0077] Comparative Example 2
[0078] Preparation of positive electrode sheet: Mix the positive electrode material lithium cobalt oxide, binder polyvinylidene fluoride, and conductive carbon black (Super P) in a mass ratio of 95.0:3.0:2.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into a slurry, and stir evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet.
[0079] The remaining preparation steps of Comparative Example 2 are the same as those of Example 1. The differences in parameters between Comparative Example 2 and Example 1 are shown in the table below.
[0080] Comparative Example 3
[0081] Preparation of positive electrode sheet: Mix the positive electrode material lithium cobalt oxide, binder polyvinylidene fluoride (PVDF), carbon nanotubes, and conductive carbon black (Super P) in a mass ratio of 97.5:1.4:0.5:0.6, use N-methylpyrrolidone (NMP) as a solvent, prepare into a slurry, and stir evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet.
[0082] The remaining preparation steps of Comparative Example 3 are the same as those of Example 1, and the specific parameter differences are shown in the table below.
[0083] Comparative Example 4
[0084] Preparation of positive electrode sheet: Mix the positive electrode material lithium cobalt oxide, binder polyvinylidene fluoride (PVDF), and conductive carbon black (SuperP) in a mass ratio of 97.5:1.5:1.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into slurry, and stir evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet.
[0085] Preparation of negative electrode sheet: negative electrode materials graphite, styrene acrylate and sodium carboxymethyl cellulose were mixed in a mass ratio of 96.5:2.0:1.5, and deionized water was used as solvent to form a negative electrode active material layer slurry. Copper foil was used as the negative electrode current collector, and the slurry of the negative electrode active material layer was coated on the negative electrode current collector. The thickness of the negative electrode active material layer on one side of the negative electrode current collector was 75 μm, and the compaction density was 1.75 g / cm 3 , and dried at 90°C to obtain the negative electrode sheet.
[0086] The remaining preparation steps of Comparative Example 4 are the same as those of Example 1.
[0087] The difference between Comparative Examples 5 and 6 and Comparative Example 4 is only the components of the negative electrode active material layer, and the rest are the same. The specific differences are shown in the table below.
[0088] The test methods of the present application are described below.
[0089] 1. Resistivity test
[0090] A resistance tester is used to test the resistivity of the positive electrode active material layer and the negative electrode active material layer. The upper and lower plane controllable pressure probes are used to directly measure the electrode pieces. An alternating current is loaded to the tested positive electrode piece or negative electrode piece. At the same time, a certain pressure (0.35T) is applied to the tested active material layer to obtain the overall resistance in the thickness direction of the electrode piece. At the same time, the area (A) and thickness (l) of the tested electrode piece are collected, and the resistivity of the tested electrode piece is derived according to the resistivity calculation formula (ρ=R*A / l).
[0091] 2. 25℃ DC resistance DCR test
[0092] At 25°C, charge the lithium-ion battery to 3.95V at 0.5C constant current, then charge to 0.05C at constant voltage; let stand for 30 minutes; discharge at 0.1C for 10s (take a point once every 0.1s and record the corresponding voltage value U1), and discharge at 1C for 360s (take a point once every 0.1s and record the corresponding voltage value U2). Repeat the charge and discharge steps 5 times. Among them, "1C" is the current value that completely discharges the battery capacity within 1 hour. The DCR of the battery is calculated according to the following formula: DCR = (U2-U1) / (1C-0.1C).
[0093] 3. Test of 3C rate performance
[0094] In an environment of 25℃, the battery was discharged to 3V at a constant current, and the first charge and discharge were performed. Constant current charging was performed at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then constant current discharge was performed at a discharge current of 0.2C until the final voltage was 3V. At this time, the discharge capacity of 0.2C was recorded, and then the battery was repeatedly charged at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then the discharge rate was set to 3C constant current discharge until the final voltage was 3V, and the discharge capacity of 3C was recorded at this time.
[0095] 3C discharge capacity retention rate = (3C discharge capacity / 0.2C discharge capacity) × 100%
[0096] 4. Cycle performance test
[0097] Charge at 1C rate to 4.2V, then change to 4.21V constant voltage charging until the current drops to 0.025C. After standing for 5 minutes, discharge at 1C rate to 3.0V, completing one cycle. Record the discharge capacity as the capacity of the lithium-ion battery. Repeat 600 cycles, record the discharge capacity as the remaining capacity of the lithium-ion battery. 600 cycle capacity retention rate = remaining capacity / initial capacity × 100%.
[0098] 5. Adhesion test
[0099] ① Disassemble the positive / negative electrodes from the fully discharged battery in a low-humidity environment, and use a customized knife die to cut the electrodes after the electrodes are dry. The length is generally 200mm*width 20-30mm; ② Take a flat thin steel plate, about 200-300mm long and 40-60mm wide. First, stick a double-sided tape (about 100-150mm long, the same width as the electrode) in the center of the steel plate, smooth it with force to ensure that the double-sided tape is tightly attached to the center of the steel plate, peel off the double-sided tape, and stick the active material layer of the electrode on the tape (it must be ensured that the electrode and the tape are matched ③ Insert the steel plate with the fixed electrode into the lower clamp of the universal tensile machine and fix it vertically. Insert the un-adhesive electrode into the upper clamp and fix it so that the electrode attached to the adhesive tape is 180° with the electrode fixed by the upper clamp. After fixing the test sample, first calibrate and clear the zero, set the test width, the electrode peeling length 50-150mm, the peeling speed 50-100mm / min, and then start the test to get the peeling strength curve and the average value.
[0100] Table 1
[0101]
[0102] Table 2
[0103]
[0104] Tables 1 and 2 show the preparation parameters and properties of Examples 1 to 5 and Comparative Examples 1 to 3, respectively, and the remaining preparation parameters not shown are the same.
[0105] As shown in Table 1 and Table 2, in Examples 1 to 5, no binder is used in the positive electrode active material layer, but carbon nanotube aggregates are added, and the carbon nanotube aggregates are interwoven to form a cage network. Binders are used in Comparative Examples 1 to 3. The DC resistance of Examples 1 to 5 is significantly lower than that of Comparative Examples 1 to 3, and the 3C discharge capacity retention rate and 600 cycle capacity retention rate of Examples 1 to 5 are significantly higher than those of Comparative Examples 1 to 3. This is because no binder is used in Examples 1 to 5, but carbon nanotube aggregates are used to stabilize the positive electrode active material layer, which avoids the adverse effects of the binder on conductivity, improves the transfer efficiency of ions and electrons, and the carbon nanotube aggregates improve the long-range conductivity, thereby improving the conductivity, kinetics and cycle performance of the lithium-ion battery.
[0106] Table 3
[0107]
[0108]
[0109] Table 4
[0110]
[0111] Tables 3 and 4 show the preparation parameters and properties of Examples 6 to 11, respectively, and the remaining preparation parameters not shown are the same.
[0112] As shown in Examples 3, 6 to 11, when the number of carbon nanotubes contained in the carbon nanotube aggregates is 2 to 1000, the DC resistance of the lithium-ion battery is small, and the 3C discharge capacity retention rate and the 600-cycle capacity retention rate are good. In particular, when the number of carbon nanotubes contained in the carbon nanotube aggregates is 500 to 1000, the lithium-ion battery performance is best. This may be because the strength of the carbon nanotube aggregates is increased, which can better stabilize the structure of the positive electrode active material layer.
[0113] As can be seen from Examples 3, 6 to 11, in the above embodiments, the diameter of the carbon nanotubes is 0.5nm to 10nm, the length is 1μm to 100μm, the diameter of the carbon nanotube aggregates is 1nm to 1000nm, and the length is 1μm to 100μm. It can be seen that when the carbon nanotubes and carbon nanotube aggregates are within the above parameter range, the lithium ion battery has good performance. Among them, the performance of Example 9 is slightly worse in the above embodiments, the DC resistance is larger, and the rate performance and cycle performance are not as good as other embodiments. This is because the diameter of the carbon nanotubes in Example 9 is the largest. At this time, the conductivity of the carbon nanotubes in its radial direction is weakened, resulting in an increase in DC resistance, which affects the rate performance and cycle performance. Therefore, the diameter of the carbon nanotubes in some embodiments of the present application is not greater than 10nm.
[0114] Table 5
[0115]
[0116] Table 6
[0117]
[0118] Tables 5 and 6 show the preparation parameters and properties of Examples 12 to 16 and Comparative Examples 4 to 6, respectively, and the remaining preparation parameters not shown are the same.
[0119] As shown in Tables 5 and 6, negative electrode active material layers with different mass ratios of graphite and carbon nanotubes were prepared in Examples 12 to 16, and no binder was used in the negative electrode active material layer, but carbon nanotube aggregates were added, and the carbon nanotube aggregates were interwoven to form a cage network. Binders were used in Comparative Examples 4 to 6. The DC resistances of Examples 12 to 16 were significantly lower than those of Comparative Examples 4 to 6, and the 3C discharge capacity retention rate and 600 cycle capacity retention rate of Examples 12 to 16 were significantly higher than those of Comparative Examples 4 to 6. This is because no binder was used in Examples 12 to 16, but carbon nanotube aggregates were used to stabilize the negative electrode active material layer, which avoided the adverse effects of the binder on conductivity, improved the transfer efficiency of ions and electrons, and the carbon nanotube aggregates improved the long-range conductivity, thereby improving the conductivity, kinetics and cycle performance of the lithium-ion battery.
[0120] It can be seen from Examples 1 to 5 and 12 to 16 that the electrode sheet proposed in the present application, whether it is a positive electrode sheet or a negative electrode sheet, can improve the conductivity, kinetic performance and cycle performance of the electrochemical device.
[0121] Table 7
[0122]
[0123]
[0124] Table 8
[0125]
[0126] Tables 7 and 8 show the preparation parameters and properties of Examples 6 to 11, respectively, and the remaining preparation parameters not shown are the same.
[0127] As shown in Examples 14, 17 to 22, when the number of carbon nanotubes contained in the carbon nanotube aggregate is 2 to 1000, the DC resistance of the lithium ion battery is small, and the 3C discharge capacity retention rate and the 600-cycle capacity retention rate are good. As shown in Examples 21 and 22, when the number of carbon nanotubes contained in the carbon nanotube aggregate is 500 to 1000, the lithium ion battery has the best performance, the smallest DC resistance, the highest 3C discharge capacity retention rate and the highest 600-cycle capacity retention rate. This may be because the increase in the number of carbon nanotube units increases the strength of the carbon nanotube aggregate, which can better stabilize the structure of the negative electrode active material layer.
[0128] As can be seen from Examples 14, 17 to 22, in the above embodiments, the diameter of the carbon nanotubes is 0.5nm to 10nm, the length is 1μm to 100μm, the diameter of the carbon nanotube aggregates is 1nm to 1000nm, and the length is 1μm to 100μm. It can be seen that when the carbon nanotubes and carbon nanotube aggregates are within the above parameter range, the lithium ion battery has good performance. Among them, Example 20 has slightly worse performance in the above embodiments, with a larger DC resistance, and the rate performance and cycle performance are not as good as other embodiments. This is because the diameter of the carbon nanotubes in Example 20 is the largest, and the conductivity of the carbon nanotubes in its radial direction is weakened, resulting in an increase in DC resistance, which affects the rate performance and cycle performance. Therefore, the diameter of the carbon nanotubes in some embodiments of the present application is not greater than 10nm.
[0129] Table 9
[0130]
[0131] Table 10
[0132]
[0133]
[0134] Tables 9 and 10 show the preparation parameters and properties of Examples 3, 23 to 29, respectively, and the remaining preparation parameters not shown are the same.
[0135] As shown in Examples 3, 24 to 25, as the compaction density of the positive electrode active material layer increases, the porosity of the positive electrode active material layer decreases accordingly, the DC resistance of the lithium-ion battery gradually decreases, and the 3C discharge capacity retention rate and the 600-cycle capacity retention rate increase oscillatingly. This may be because the increase in the compaction density reduces the gap between the positive electrode materials, which is beneficial to the transmission of ions and electrons and can increase the volume energy density. However, if the compaction density is further increased, it may cause the positive electrode material particles to rupture, increase the consumption of the electrolyte, and may affect the cycle performance.
[0136] As shown in Examples 3, 25 to 29, when the positive electrode material is lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide or lithium nickel cobalt aluminum oxide, the comprehensive performance of the lithium ion battery is good, among which the performance is best when the positive electrode material is lithium cobalt oxide.
[0137] Table 11
[0138]
[0139]
[0140] Table 12
[0141]
[0142] Tables 11 and 12 show the preparation parameters and properties of Examples 14, 30 to 37, respectively, and the remaining preparation parameters not shown are the same.
[0143] As shown in Examples 14, 30 to 33, with the increase in the compaction density of the negative electrode active material layer, the DC resistance of the lithium-ion battery gradually decreases, and the 3C discharge capacity retention rate and the 600-cycle capacity retention rate oscillate and increase. This may be because the increase in the compaction density reduces the gap between the negative electrode materials, which is beneficial to the transmission of ions and electrons and can increase the volume energy density. However, if the compaction density is further increased, it may cause the negative electrode material particles to rupture, increase the consumption of the electrolyte, and may affect the cycle performance.
[0144] As shown in Examples 14 and 34 to 37, when the negative electrode material is graphite, silicon oxide, lithium titanate, silicon or hard carbon, the comprehensive performance of the lithium-ion battery is good, among which the performance is best when the negative electrode material is hard carbon.
[0145] Table 13
[0146]
[0147] Table 14
[0148]
[0149] Table 13 and Table 14 show the preparation parameters and properties of Example 38, respectively.
[0150] In Example 38, no binder is added to the positive electrode and the negative electrode. From the performance test results of Example 38, it can be seen that it has lower resistivity of the positive electrode active material layer and the negative electrode active material layer, and has low DC resistance, high 3C discharge capacity retention rate and 600 cycle capacity retention rate, and its comprehensive performance is the best.
[0151] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.
Claims
1. An electrode, characterized in that: The electrode comprises a current collector and an active material layer located on one side or both sides of the current collector, wherein the active material layer comprises an active material and a conductive agent; the conductive agent comprises carbon nanotubes, and the active material layer comprises rope-shaped carbon nanotube aggregates formed by the carbon nanotubes, wherein the carbon nanotube aggregates are interwoven to form a cage-like network, and the active material is wrapped inside the cage-like network; The diameter of the carbon nanotube is 0.5nm to 7nm; The carbon nanotube aggregate has a rope-like structure formed by 10 to 1000 carbon nanotubes entangled with each other.
2. The electrode according to claim 1, characterized in that Satisfy at least one of the following: (a) based on the total mass of the active material layer, the mass percentage of the carbon nanotube aggregates is 0.5% to 5%; (c) the carbon nanotubes have a length of 1 μm to 100 μm; (d) The carbon nanotube aggregate has a diameter of 1 nm to 1000 nm and a length of 1 μm to 100 μm.
3. The electrode according to claim 1, characterized in that Satisfy at least one of the following: (a) the thickness of the carbon nanotube aggregates on the surface of the active material particles is 10 nm to 1000 nm; (b) One network gap in the cage-like network includes 1 to 50 particles of the active material.
4. The electrode according to claim 1, characterized in that The active material has a Dv50 of 1 μm to 30 μm.
5. The electrode according to claim 1, characterized in that The electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and at least one of the following conditions is satisfied: (a) The compaction density of the positive electrode active material layer ρ1≥3.0 g / cm 3 ; (b) the porosity n1 of the positive electrode active material layer satisfies: 20% ≥ n1 ≥ 15%; (c) the resistivity of the positive electrode active material layer is: 0.1Ω*㎝ to 100Ω*㎝; (d) the bonding force of the positive electrode active material layer is ≥ 1 N / m; (e) The active material is a positive electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium rich material, sulfur or sulfur-based compounds.
6. The electrode according to claim 1, characterized in that The electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the compaction density ρ1 of the positive electrode active material layer satisfies: 4.25 g / cm 3 ≥ρ1≥2.3g / cm 3 .
7. The electrode according to claim 1, characterized in that The electrode is a negative electrode, the current collector is a negative electrode current collector, the active material layer is a negative electrode active material layer, and at least one of the following conditions is satisfied: (a) The compaction density of the negative electrode active material layer ρ2≥1.3 g / cm 3 ; (b) the porosity n2 of the negative electrode active material layer satisfies: 35% ≥ n2 ≥ 25%; (c) the resistivity of the negative electrode active material layer is 0.01Ω*㎝ to 50Ω*㎝; (d) the bonding force of the negative electrode active material layer is ≥ 1 N / m; (e) The negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, a silicon-based material, a tin-based material, a lithium metal material or a carbon material.
8. The electrode according to claim 1, characterized in that The electrode is a negative electrode, the active material layer is a negative electrode active material layer, and the compaction density ρ2 of the negative electrode active material layer satisfies: 1.85 g / cm 3 ≥ρ2≥1.35g / cm 3 .
9. An electrochemical device, characterized in that: including electrodes; The electrode is the electrode according to any one of claims 1 to 8.
10. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 9.
Citation Information
Patent Citations
Highly efficient electrodes enabled by segregated networks
EP3680961A1